2021
DOI: 10.1177/00048674211047189
|View full text |Cite
|
Sign up to set email alerts
|

A biomarker and endophenotype for anorexia nervosa?

Abstract: Objective: Recent research has suggested that a type of atypical eye movement, called square wave jerks, together with anxiety, may distinguish individuals with anorexia nervosa from those without anorexia nervosa and may represent a biomarker and endophenotype for the illness. The aim of this study was to identify the presence of this proposed marker in individuals currently with anorexia nervosa relative to healthy controls, and to identify the state independence and heritability of this putative marker by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Across groups, exploratory Pearson's correlation analyses will also be conducted between S-EDE-Q, STAI scores, and BMI and the outcome measures associated with the eye-tracking data (see Table 1, for a detailed view). Additionally, if significant differences are found between STAI scores and SWJ rate, consistent with previous literature [31,32], a discriminant analysis will be performed on the entire sample to elucidate to what extent both measures correctly classify group membership (participants with subclinical ED symptomatology vs. control participants). Alpha will be set at 0.05 for all analyses.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Across groups, exploratory Pearson's correlation analyses will also be conducted between S-EDE-Q, STAI scores, and BMI and the outcome measures associated with the eye-tracking data (see Table 1, for a detailed view). Additionally, if significant differences are found between STAI scores and SWJ rate, consistent with previous literature [31,32], a discriminant analysis will be performed on the entire sample to elucidate to what extent both measures correctly classify group membership (participants with subclinical ED symptomatology vs. control participants). Alpha will be set at 0.05 for all analyses.…”
Section: Discussionmentioning
confidence: 60%
“…As Malcom and Phillipou [18] noted in their recent review, demonstrating a relationship with illness is one of the first steps in determining biomarkers and endophenotypes. As illustrative example, first Phillipou et al [33] showed the existence of specific eye movement anomalies in patients with AN and only after these findings, they amplified the scope of their study and were able to identify the state-independence of these eye movement abnormalities [32]. Following this line of reasoning, we will investigate whether the aforementioned eye movement abnormalities detected are, in this case, associated in young-adult women with subclinical symptomatology.…”
Section: Study Objectives and Hypothesismentioning
confidence: 85%
See 2 more Smart Citations
“…Speci cally, they showed an increased rate of saccadic intrusions named square wave jerks (SWJs; these are horizontal, involuntary, saccadic intrusions that interrupt xation). Recently, Philipou et al'.s [29] identi ed the state independence and heritability of this possible biomarker. According to the results, they found that patients with AN, patients' weight-restored from the illness, and sisters of people with AN, made signi cantly more SWJs than healthy controls.…”
Section: Introductionmentioning
confidence: 99%